Cardiovascular Safety of Clonidine and Dexmedetomidine in Critically Ill Patients after Cardiac Surgery. (7th May 2020) - Grest, Angelina; Kurmann, Judith; Müller, Markus; Jeger, Victor; Krüger, Bernard; Spahn, Donat R.; Bettex, Dominique; Rudiger, Alain
Abstract : Purpose . The aim of this retrospective study was to assess the haemodynamic adverse effects of clonidine and dexmedetomidine in critically ill patients after cardiac surgery. Methods . 2769 patients were screened during the 30-month study period. Heart rate (HR), mean arterial pressure (MAP), and norepinephrine requirements were assessed 3-hourly during the first 12 hours of the continuous drug infusion. Results are given as median (interquartile range) or numbers (percentages). Results . Patients receiving clonidine ( n  = 193) were younger (66 (57–73) vs 70 (63–77) years, p = 0.003 ) and had a lower SAPS II (35 (27–48) vs 41 (31–54), p = 0.008 ) compared with patients receiving dexmedetomidine ( n  = 141). At the start of the drug infusion, HR (90 (75–100) vs 90 (80–105) bpm, p = 0.028 ), MAP (70 (65–80) vs 70 (65–75) mmHg, p = 0.093 ), and norepinephrine (0.05 (0.00–0.11) vs 0.12 (0.03–0.19) mcg/kg/min, p < 0.001 ) were recorded in patients with clonidine and dexmedetomidine. Bradycardia (HR < 60 bpm) developed in 7.8% with clonidine and 5.7% with dexmedetomidine (p = 0.51 ). Between baseline and 12 hours, norepinephrine remained stable in the clonidine group (0.00 (−0.04–0.02) mcg/kg/min) and decreased in the dexmedetomidine group (−0.03 (−0.10–0.02) mcg/kg/min, p = 0.007 ). Conclusions . Dexmedetomidine and the low-cost drug clonidine can both be used safely in selected patients after cardiac surgery.